IZIN USAHA PERTAMBANGAN MINERAL DAN BATUBARA DALAM KAITAN DENGAN PENGELOLAAN DAN PERLINDUNGAN LINGKUNGAN HIDUP (FIQH AL-BI'AH) - Hemi Faradila (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Act Number 4 of 2009 about Mineral and Coal Mining allows latitude in exploiting natural resources. However, the act tends to claim ‘resource used oriented law’. The purpose of this research is to devise whether Act Number 4 of 2009 about Mineral and Coal has accommodated the aspect of environmental’s protection and the principles of environmental’s management following Act Number 32 of 2009 about Environmental’s Protection and Management as known as UUPPLH, especially over licensing of mineral and coal as preventive juridical. This research is based on prescriptive analysis by descriptive and juridical normative approaches. A principle that is implemented in this research is the Principle of State Responsibility and Principle of Sustainable Development and Environmental Concept. The result of this research concludes that Act Number 4 of 2009 about Mineral and Coal Mining has not accommodated optimally yet regarding environmental’s protection over mineral and coal mining business. Based on this fact, mineral and coal mining projects cause pollution and environmental damages sustainably. Whereas, based on a substantial law system, the rule of the law normatively has autonomous force as an idea that determines public interest in economic and environmental aspects. The contribution of this research will be recommended to the development of environmental law and environmental sustainability.